1977
DOI: 10.1128/jb.132.3.790-795.1977
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of a non-metabolizable fatty acid on the growth of Escherichia coli: role of metabolism and outer membrane integrity

Abstract: The inhibitory action of decanoic acid on both Escherichia coli K-12/154 (normal lipopolysaccharide) and E. coli RC59 (defective lipopolysaccharide) was studied. A correlation was found between the doubling time of E. coli 154 growing in different media and the lethal effect of 0.4% decanoic acid on this bacterium. Decanoic acid (0.4%) exerted a lytic action on glucose-starved and NaN 1-inhibited cells of E. coli 154 and RC59. Exponentially growing cultures of both strains were not affected by the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The growth of S. carnosus 833 was largely independent of the chain length of the methyl ester (3.5 mM) with only a small increase in the growth rate (W) in the presence of methyl decanoate, methyl laurate and methyl oleate and a small decrease for methyl palmitate (Table 1). These results are consistent with those obtained in Escherichia coli for which methyl decanoate (23.2 mM) had no e¡ect on growth [10,11]. Those authors reported an inhibitory e¡ect of free decanoic acid.…”
Section: E¡ect Of Methyl Esters On the Growth Of S Carnosus 833supporting
confidence: 91%
“…The growth of S. carnosus 833 was largely independent of the chain length of the methyl ester (3.5 mM) with only a small increase in the growth rate (W) in the presence of methyl decanoate, methyl laurate and methyl oleate and a small decrease for methyl palmitate (Table 1). These results are consistent with those obtained in Escherichia coli for which methyl decanoate (23.2 mM) had no e¡ect on growth [10,11]. Those authors reported an inhibitory e¡ect of free decanoic acid.…”
Section: E¡ect Of Methyl Esters On the Growth Of S Carnosus 833supporting
confidence: 91%
“…Two phenomena that lower the energy status of the cell could account for these effects. Firstly, the presence of toxic levels of toluene severely perturbs the membrane, bringing about the passive flux of protons across the membrane (Fay and Farias, 1977; Leao and Van Uden, 1984; Cartwright et al ., 1986; Sikkema et al ., 1994), thus dissipating the PMF (Cartwright et al ., 1986; Sikkema et al ., 1994). Secondly, toluene induces expression of the solvent‐resistance pump SrpABC (Kieboom et al ., 1998a,b), which is a proton‐dependent solvent‐efflux system (Isken and de Bont, 1996; Isken et al ., 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Human fecal lipids contain a mixture of long chain free fatty acids such as C16:0, C I8:1, C18:2, and C 20 or more, which are bactericidal for gonococci [24] . The mechanism of the antimicrobial action of AA seems to be by inducing leakage and even lysis of bacterial cell membranes [25] , [26] as well as various cellular metabolic effects, including but not limited to inhibition of respiratory activity, effects on transportation of amino acids, and uncoupling of oxidative phosphorylation [27] , [28] , [29] , [30] .…”
Section: Macrophage Aa Has Antimicrobial Actionsmentioning
confidence: 99%